Parental Unemployment and the Transition into Tertiary Education: Can Institutions Moderate the Adverse Effects?. (1st February 2020) - Lindemann, Kristina; Gangl, Markus
Abstract: We examine how parental unemployment affects children's transition to postsecondary education in different institutional contexts. Drawing on theoretical perspectives in intergenerational mobility research and sociology of higher education, we estimate the extent to which these intergenerational effects depend on social and education policies. We use data from five longitudinal surveys to analyze the effects of parental unemployment on entry to postsecondary education in 21 countries. The results of multilevel regression analysis show that in contexts that provide better insurance against unemployment, in terms of generous earnings replacement, the adverse effect of parental unemployment is alleviated. Moreover, entry gaps between youth from unemployed and employed households are smaller in tertiary education systems with more opportunity-equalizing education policies that provide more financial support to students and reduce the role of private expenditure. Some evidence also indicates that policies are more relevant for children of less-educated unemployed parents.